Hamlet Plangization: Efforts to Strengthen Regional Identity and Accessibility in Sindupaten Village - Aziz Hakim; Muhammad Mukhlis; Indrawati Aris Tyarini (Asskruie: Jurnal Pengabdian Kepada Masyarakat, 2025)
Sindupaten Village is an administrative area located in Kertek District, Wonosobo Regency, which faces challenges in its navigation system due to the lack of directional signboards. This condition causes difficulties for visitors, public service officers, and delivery couriers in locating specific addresses. The absence of adequate wayfinding infrastructure also reduces mobility efficiency and weakens the village’s spatial identity. The Plangisasi Dusun (Village Signboard Installation) program aims to strengthen spatial identity, improve accessibility, and enhance the organization of public spaces in Sindupaten Village. This community service project employed a Participatory Action Research (PAR) approach involving local residents in the planning, design, and installation processes. Strategic signboard placement points were determined using movement network theory to identify the main routes of community and visitor movement. The results show a significant improvement in address search efficiency, with the average search time reduced by approximately 40%. In addition, residents reported a stronger sense of belonging toward their village environment. The initiative also increased community awareness of the importance of informative and collaborative spatial design in supporting local public services. Therefore, the Plangisasi Dusun program has proven effective in enhancing social connectivity, strengthening local identity, and promoting sustainable village development through participatory engagement.